Pengaruh Profitabilitas Terhadap Harga Saham Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2021-2024 - Deswita Erya Kumala Sari; Alva Yenica Nandavita; Thoyibatun Nisa; Witantri Dwi Swandini (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the effect of Net Profit Margin (NPM), Earning Per Share (EPS), Gross Profit Margin (GPM), Return on Assets (ROA), and Return on Equity (ROE) on stock prices in mining companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2024. This study uses a quantitative method with an associative approach and purposive sampling technique, resulting in 76 observations. Data analysis was performed using descriptive statistics, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination with the help of SPSS version 27. The results show that, partially, NPM and GPM have a significant effect on stock prices, while EPS, ROA, and ROE do not have a significant effect. Simultaneously, all independent variables significantly affect stock prices with a significance value of 0.011 (<0.05). The coefficient of determination (R²) value of 0.092 indicates that the independent variables can explain 9.2% of the variation in stock prices, while 90.8% is influenced by other factors outside the research model.